2015
DOI: 10.1021/acs.organomet.5b00455
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oligomerization and [2 + 2 + 2] Cycloaddition of Terminal Alkynes from Simple Actinide Precatalysts

Abstract: A catalyzed conversion of terminal alkynes into dimers, trimers, and trisubstituted benzenes has been developed using the actinide amides U[N(SiMe 3 ) 2 ] 3 (1) and [(Me 3 Si) 2 N] 2 An[κ 2 -(N,C)-CH 2 Si(CH 3 )N(SiMe 3 )] (An = U (2), Th (3)) as precatalysts. These complexes allow for preferential product formation according to the identity of the metal and the catalyst loading. While these complexes are known as valuable precursors for the preparation of various actinide complexes, this is the first demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 178 publications
0
24
0
Order By: Relevance
“…The phenyl group has a weak π-donor and inductive withdrawing character 12 that makes phenylacetylene a mild electron deficient alkyne. 13 The Gibbs energy profile obtained for the [2+2+2] cyclotrimerisation of phenylacetylene catalysed by [Rh(BIPHEP)] + is shown in Scheme 3. There is a preactivation scenario that transforms A0 to A2 in an exergonic process by ca.…”
Section: Resultsmentioning
confidence: 99%
“…The phenyl group has a weak π-donor and inductive withdrawing character 12 that makes phenylacetylene a mild electron deficient alkyne. 13 The Gibbs energy profile obtained for the [2+2+2] cyclotrimerisation of phenylacetylene catalysed by [Rh(BIPHEP)] + is shown in Scheme 3. There is a preactivation scenario that transforms A0 to A2 in an exergonic process by ca.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to isolate the intermediates generated and characterisation by crystallisation were unsuccessful, however previous studies have shown that activation of the thorium complex 3 with terminal alkyne similarly results in complete displacement of the amido moieties. 53 It is worth note that the order of addition of the reagents to the precatalyst solution did not markedly affect the reaction rate or product distribution. The nature of the REH substrate additionally affects the outcome of the insertion product ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, we have shown that a series of simple amido–actinide complexes of the formula U[N(SiMe 3 ) 2 ] 3 ( 1 ) and [(Me 3 Si) 2 N] 2 An[κ 2 -( N , C )–CH 2 Si(CH 3 ) 2 N(SiMe 3 )] (An = U ( 2 ), Th ( 3 )) ( Fig. 1 ) are capable of effecting the efficient oligomerisation or cyclotrimerisation of terminal alkynes, 53 the sole example of a catalytic transformation employing this class of complexes prior to the work described in this study. These complexes are generated in a one-pot process using readily available starting materials and have already shown impressive stoichiometric reactivity, 54 , 55 making them exceptionally attractive in their use as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…11,15 For example, Arnold and coworkers have used an organothorium metallacycle precatalyst, [(Me 3 Si) 2 N]Th[k 2 -(N,C)-CH 2 Si(CH 3 )N(SiMe 3 )], to regioselectively oligomerize terminal alkynes producing organic enynes and this demonstrates the first example of using a Th catalyst such as this in C-C bond formation. 18 Although all of these methods have aided in the understanding of the chemistry of the actinides, they require laborious preparation and, being either air or moisture sensitive, have short shelf-lives. In contrast to these organoactinide catalysts, actinide salts offer longer shelf-lives and increased ease of use.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, simple, sterically unencumbered actinide centers have rarely been reported in the literature. 17,18 Few reactions have been reported with simple actinide salts, 17,18,26 and no catalytic reactions have been reported using simple thorium salts. …”
Section: Introductionmentioning
confidence: 99%